Sibling curves of quadratic polynomials. Issue 2 (3rd April 2017) - Wiggins, Harry; Harding, Ansie; Engelbrecht, Johann
Abstract: Sibling curves were demonstrated in [1, 2] as a novel way to visualize the zeroes of real valued functions. In [3] it was shown that a polynomial of degree n has n sibling curves. This paper focuses on the algebraic and geometric properites of the sibling curves of real and complex quadratic polynomials.